1995
DOI: 10.1172/jci118091
|View full text |Cite
|
Sign up to set email alerts
|

The role of fibrinogen D domain intermolecular association sites in the polymerization of fibrin and fibrinogen Tokyo II (gamma 275 Arg-->Cys).

Abstract: IntroductionIntermolecular end-to-middle domain pairing between a thrombin-exposed 'A' polymerization site in Invest. 1995Invest. . 96:1053Invest. -1058

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 26 publications
4
62
1
Order By: Relevance
“…The positioning of end-to-end-crosslinked ␥ chains has been adjusted from the originally proposed location at the extreme ends of the D domain (DD-long; ref. 20) to take into account recent data indicating that their location at the D:D site is not a realistic possibility (1,21,25,27). brated with 20 mM Hepes and 5 mM NaCl, pH 7.0 buffer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The positioning of end-to-end-crosslinked ␥ chains has been adjusted from the originally proposed location at the extreme ends of the D domain (DD-long; ref. 20) to take into account recent data indicating that their location at the D:D site is not a realistic possibility (1,21,25,27). brated with 20 mM Hepes and 5 mM NaCl, pH 7.0 buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the ''end-to-end'' crosslinking idea received somewhat revised support from studies of crystals of crosslinked D dimer fragments (21), in which crosslinked C-terminal ␥ chains, though not situated at the extreme end of the molecule as originally envisioned, were inferred nevertheless to traverse the abutting D domains in an end-to-end alignment. However, several independent lines of evidence, beginning with reports by Selmayr et al (22,23), have indicated that the crosslinked ␥ chain segments in fibrin do not straddle the ends of adjacent D domains but rather tend to extend transversely between each fibril strand (1,(24)(25)(26). Evidence in favor of the transverse bond arrangement includes among the above cited articles, the electron microscopic demonstration of double-stranded crosslinked fibrinogen fibrils, visualization of bridging filaments representing transversely positioned ␥ chains within crosslinked fibrinogen fibrils (1) and in crosslinked D-fibrin-D complexes (26), and evidence indicating that the abutting ends of fibrin D domains where end-to-end intermolecular contacts are now recognized to occur (the so-called D:D site) (1,21,25), do not as first proposed (20), contain the C-terminal ␥ chain segment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…a dysfibrinogen with an A␣ Arg-16 3 Cys substitution resulting in defective thrombin-catalyzed release of fibrinopeptide A due to the mutation at the P1 site for thrombin, and a dysfibrinogen with a ␥ Arg-275 3 Cys substitution, manifesting impaired D:D self-association (16).…”
Section: Methodsmentioning
confidence: 99%
“…These A:a interactions mediate the formation of double-stranded protofibrils with half-staggered overlap between molecules in different strands [4]. The end-to-end alignment of monomers in each protofibril strand requires so-called D:D interaction, which abuts the -chain of two adjacent molecules [5]. In the second step, these protofibrils grow in length and thrombin cleaves FpB, which exposes a new N-terminal segment, knob 'B', which likely interacts with hole 'b' in the  module of the D region of another molecule to promote lateral aggregation of the protofibrils [6], resulting in the formation of thicker fibers and finally an insoluble fibrin clot consisting of a multi-stranded and branched fiber network [7].…”
Section: Introductionmentioning
confidence: 99%